2014
DOI: 10.3389/fmicb.2014.00309
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere heterogeneity shapes abundance and activity of sulfur-oxidizing bacteria in vegetated salt marsh sediments

Abstract: Salt marshes are highly productive ecosystems hosting an intense sulfur (S) cycle, yet little is known about S-oxidizing microorganisms in these ecosystems. Here, we studied the diversity and transcriptional activity of S-oxidizers in salt marsh sediments colonized by the plant Spartina alterniflora, and assessed variations with sediment depth and small-scale compartments within the rhizosphere. We combined next-generation amplicon sequencing of 16S rDNA and rRNA libraries with phylogenetic analyses of marker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
78
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 66 publications
12
78
1
Order By: Relevance
“…Indeed, abundant bacteria that are predicted sulfur oxidizers have been detected in marine sediments attached to seagrass roots (27), and terminal restriction fragment length polymorphism (T-RFLP) community profiling (43) of root surfaces in a single European seagrass bed has suggested similar patterns in Epsilonproteobacteria community dominance (44). This result is also consistent with observations that Spartina cordgrasses in coastal salt marshes are associated with abundant sulfur-oxidizing bacteria (45).…”
Section: Figsupporting
confidence: 73%
“…Indeed, abundant bacteria that are predicted sulfur oxidizers have been detected in marine sediments attached to seagrass roots (27), and terminal restriction fragment length polymorphism (T-RFLP) community profiling (43) of root surfaces in a single European seagrass bed has suggested similar patterns in Epsilonproteobacteria community dominance (44). This result is also consistent with observations that Spartina cordgrasses in coastal salt marshes are associated with abundant sulfur-oxidizing bacteria (45).…”
Section: Figsupporting
confidence: 73%
“…However, we observed greater abundances of Gammaproteobacteria, which are adapted to relatively high oxygen levels (Thomas et al. (), within the short‐form rhizosphere, that cannot be readily explained by temporal differences in root activity between the growth forms nor by differences in abiotic conditions (i.e., we would expect lower numbers of these bacteria in short‐form habitat due to the more saturated soil, as compared to tall form locations).…”
Section: Discussionmentioning
confidence: 57%
“…Within the rhizosphere, we found significant differences in community composition depending on whether bacteria were collected from the roots of short‐form or tall‐form S. alterniflora (Figure ). Other studies within northeastern US marshes have reported differences in bacteria among growth forms too, including the entire community in bulk soil (Bowen, Crump, Deegan, & Hobbie, ), and sulfur oxidizers in the rhizosphere (Thomas, Giblin, Cardon, & Sievert, ; although they did not explicitly mention growth forms, their Site 1 was located along the creekbank and thus presumably contained tall form plants, and their Site 2 was on the marsh platform so likely would have consisted of short‐form plants). The major taxonomic differences in our analysis were that rhizosphere microbes associated with tall form plants were dominated by bacteria in the Class Deltaproteobacteria, whereas short‐from microbes were predominantly from the Class Gammaproteobacteria (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations